ANALISIS INVESTASI PERUMAHAN PURI MAHKOTA MUKTIWARI DI KABUPATEN BEKASI - ALDI ALDI; Dewi Yustiarini; Siti Nurasiyah (Universitas Pendidikan Indonesia (UPI), 2023)
As the population grows rapidly and the standard of living increases, the demand for housing will increase. One way to meet housing needs is to build housing. Housing development must be in accordance with careful planning in determining the investment model to be made in housing development. The initial stages of housing development start from surveying the location, number and type of houses to be built, marketing, to selling to consumers. The housing development process must also be calculated economically with the investment method, to find out whether this housing can be economically profitable or not. Based on the calculation of investment analysis with an investment period of 6 years, the Net Present Value (NPV) is Rp. 33,716,228,908 (NPV0), the Internal Rate of Return (IRR) is 23,18% (IRRMARR), Payback Period (PP) in the 3rd year to 11th months is smaller than the 6 year investment period, Benefit Cost Ratio (BCR) is 1.42 (BCR 1), and Break Event Point (BEP) gets a percentage for type 30/60 of 90% with 132 units, type 36/60 by 69% with 207 units, type 36/72 by 56% with 172 units, and type 48/84 by 48% with 32 units. And from the sensitivity analysis results it is known that housing investment Puri Mahkota Muktiwari will still be feasible if the increase in investment costs is less than 20.15%, the decrease in the occupancy rate is not more than 16.74%, the decrease in the selling price level is not more than 16.7% and the increase in loan interest rates is less of 122.22%.Â Keywords :Â Investment Feasibility,Housing, industrial estate, Investment analysis, Sensitivity Analys